The Influence Of Social Media Marketing, Customer Experience, And Perceived Value On Purchase Intention Through Relationship Quality - Febry Valentina; Harits Hijrah Wicaksana (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This research seeks to examine how social media marketing, customer experience, and perceived value impact purchase intention, with relationship quality serving as a mediating factor among TikTok Shop users in Tangerang Regency. A total of 165 respondents aged 17 to 35, who have made purchases via TikTok Shop, participated in the study. Data were gathered through an online survey and analyzed using the PLS-SEM approach. The findings reveal that social media marketing, customer experience, and perceived value positively contribute to enhancing relationship quality. Moreover, these variables affect purchase intention both directly and indirectly through their impact on relationship quality. These results emphasize the significance of digital marketing efforts that prioritize building strong relationships, delivering positive user experiences, and enhancing perceived value to boost consumer purchase intention. The study provides valuable insights for developing more effective digital marketing strategies on the TikTok platform.